2020
DOI: 10.3389/fphys.2020.01089
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Non-lethal Doses of Natural Insecticides Spinetoram and Azadirachtin on Helicoverpa punctigera (Native Budworm, Lepidoptera: Noctuidae) Under Laboratory Conditions

Abstract: Helicoverpa punctigera (native budworm) is an important pest species in crops across Australia. From the third instar onward, this species causes severe damage to crop plants: therefore, caterpillars need to be managed at an early stage of their development. In our experiment, we raised H. punctigera on an artificial diet, which included different concentrations of the natural insecticides Spinetoram and Azadirachtin. The survival of the larvae, growth and body mass gain was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Spinetoram is a semisynthetic insecticide obtained by synthetic modification of spinosyn biological insecticides ( Betz and Andrew, 2020 ). It acts on synaptic transmission ( Piovesan et al, 2020 ), and studies have shown that exposure to high levels of spinetoram threatens the survival of bumblebees ( Besard et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Spinetoram is a semisynthetic insecticide obtained by synthetic modification of spinosyn biological insecticides ( Betz and Andrew, 2020 ). It acts on synaptic transmission ( Piovesan et al, 2020 ), and studies have shown that exposure to high levels of spinetoram threatens the survival of bumblebees ( Besard et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…AMMI stability values (ASVs) differed in terms of stability of root weight between three treatments (variant based on the sums of effective temperatures (F1); the heat sums (F2); pest alerts (S)) (Table 2). Following the work of Purchase et al [17], a stable protective treatment is characterized by an ASV close to zero. According to this definition, it was demonstrated that treatments S (ASV 2.291) and F1 (ASV 2.800) were most stable, and the K2 variant (15.618) was least stable (Table 2).…”
Section: Root Weightmentioning
confidence: 99%
“…Similarly, cutworms, or surface caterpillars, damage sugar beet plants and have negative impacts on obtained crop yields. Several species are known to damage sugar beet, including Agrotis spp., Euxoa spp., and Xestia c-nigrum (L.) Central and Northern Europe and the USA), Peridroma saucia (Hübner), Crymodes devastator (Brace), and Feltia ducens (Walker) (in the USA); in addition to those also mentioned the larvae of many other moths such as Hydraecia micacea, Loxostege sticticalis (L.), Scrobipalpa ocellatella Boyd, Spodoptera spp., and Pseudaletia unipunctata (Haworth) can also damage the foliage of beet plants [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have demonstrated the suppressive effects of AZN on 250 species of insect pests, especially Lepidoptera (Martinez and Emden 2001;Liang et al 2003;Seljasen and Meadow 2006;Pineda et al 2009;Ünsal and Güner 2016;Boadu et al 2011;Darabian and Yarahmadi 2017;Zhong et al 2017;Heibatian et al 2018;Qin et al 2019;Betz and Andrew 2020). The objectives of the present study were to i) determine an efficient AZN concentration for pest management by dose dependent AZN toxicity and ii) assess the life cycle of S. ocellatella on sugar beet plants exposed to sublethal concentrations of AZN.…”
Section: Introductionmentioning
confidence: 96%